Open Fracture of the Acromion: An Isolated Injury with Oblique-Type Fracture - Mohammad O. Alawad; Saleh Alharthi; Jameel Mahmoud; Basam Alanazi; Saad Surur (Case Reports in Orthopedics)
Open acromial fractures are a rare set of fractures. We report a case of Gustilo IIIA open acromial fracture (14A2 as per OTA scapular fracture classification) that was isolated from any other injury. Our patient had a good recovery and showed excellent clinical outcome after irrigation and screw fixation of the acromial fracture. We also reviewed the literature for other cases of open acromial fracture.